Title IX Information Increases Female Collegiate Athletes' Intent to Seek Help - Erika Guenther; Elizabeth Sorensen; Lance Champagne (Journal of Intercollegiate Sport, 2023)
Female intercollegiate student athletes continue to lack knowledge of their pregnancy rights. Uninformed athletes may react to pregnancy by concealing it or worse, risking their health and the health of their fetus. This study aimed to determine baseline knowledge in a contemporary sample of female athletes and to determine the extent that pregnancy rights information affected intent to seek help for pregnancy. A convenience sample of 146 female student athletes from nine teams at one NCAA Division I university (mean age 20.2 years) responded to an anonymous, online, author-designed survey. Halfway through the survey, pregnancy rights information (the intervention) was provided. Prior to the intervention most participants were unaware of pregnancy rights. If they experienced pregnancy and particularly if they decided to remain pregnant to the completion of their pregnancy, participants expected to be cut from the team, lose financial aid, and be unable to return to the team. Following the intervention, participants were significantly less likely to expect negative consequences and significantly more likely to seek help from athletic staff. Those who were aware of federal pregnancy rights were significantly unlikely to be aware of NCAA protections. A question yet unanswered is who is or should be responsible for ensuring that federal and NCAA pregnancy protections are known to female student athletes who may experience pregnancy. Recommendations to the NCAA and its member schools include more vigorous, effective provision of complete, timely pregnancy rights information.